Spring elements for rewod energy harvesters: Printing emulsion templates to manufacture macroporous polymers - Menner,A; Jiang,Q; Bismarck,A (2016)
We aim to develop an energy harvesting device that allows charging a battery of e.g. a smart phone while jogging simply by converting mechanical energy into electrical energy using the "REWOD" (Reverse-Electrowetting-On-Dielectric) effect. A vital part of such an energy harvester are highly interconnected and flexible macroporous polymer springs which are required to improve the harvesting efficiency. We use emulsion templates as inks and syringe print them on the harvester's dielectric in any desired shape and dimension (e.g. cages having dimensions ranging from 2mm x2mm down to 0.5mmx0.5mm which are up to 400 μm high). UV-polymerisation of the polyurethane diacrylate/ethylhexyl acrylate based continuous phase of the emulsion templates and subsequent removal of the internal phase yields in highly flexible macroporous polymer springs: cyclic compression tests confirmed that they can repeatedly be compressed by 70% without experiencing permanent plastic deformation. Furthermore, we will present a REWOD energy harvesting prototype achieving a capacity change of up to 1000pF upon mechanical deformation.